PELAKSANAAN PROMOSI EKOWISATA TAMAN NASIONAL TESSO NILO OLEH WORLD WILDLIFE FUND DI DESA LUBUK KEMBANG BUNGA KECAMATAN UKUI KABUPATEN PELALAWAN - Saepul Ulum; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to describe the implementation of Ecotourism Promotion of Tesso Nilo National Park in the village of Lubuk Flower Bungo District of Ukui Pelalawan, and how the responses of visitors on the Implementation of the Promotion, in the form of Advertising, Public Relations word of mouth, personal selling and sales promotion. This study uses a quantitative method with a descriptive approach to solve problems in the lift. The sample in this study as many as 55 people were taken by using accidental sampling. While data collection techniques in this study using observation, questioner, interview and documentation. By using a Likert scale as a measure to determine the length of the short interval. Based on the research that has been done, responsden response to the Implementation of Ecotourism Promotion of Tesso Nilo National Park has been good. And proved to be a leading tourist attraction regency. Keywords: Tourism, Promotion Execution, Tesso Nilo National Park